2021
DOI: 10.3390/ijerph182312272
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Structured Intervention to Improve Motor Skills in Preschool Children: Results of a Randomized Controlled Trial Nested in a Cohort Study of Danish Preschool Children, the MiPS Study

Abstract: The preschool age seems to be decisive for the development of motor skills and probably the most promising time-window in relation to improvement of motor skills. This trial investigates the effect of an intensive structured intervention to improve motor skills in 3–6-year-old preschool children. A total of 471 Danish preschool children participated in a cluster randomized controlled trial. The intervention was to enhance motor skills, including predefined minimum criteria. Motor skills were measured using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Our partly positive intervention effects for locomotor skills, object control skills, and PA align with findings in previous meta-analyses and systematic reviews showing beneficial effects of preschool PA interventions on FMS [ 9 , 26 – 28 ] and objectively measured PA [ 63 , 64 ]. Our null-finding for balance aligns with some previous studies [ 31 , 65 , 66 ] but contradicts others [ 67 ]. Of the relevant studies in the meta-analysis by Koolwijk et al [ 28 ], most studies showed positive findings on one or several FMS outcomes, mainly on object control skills.…”
Section: Discussionsupporting
confidence: 81%
“…Our partly positive intervention effects for locomotor skills, object control skills, and PA align with findings in previous meta-analyses and systematic reviews showing beneficial effects of preschool PA interventions on FMS [ 9 , 26 – 28 ] and objectively measured PA [ 63 , 64 ]. Our null-finding for balance aligns with some previous studies [ 31 , 65 , 66 ] but contradicts others [ 67 ]. Of the relevant studies in the meta-analysis by Koolwijk et al [ 28 ], most studies showed positive findings on one or several FMS outcomes, mainly on object control skills.…”
Section: Discussionsupporting
confidence: 81%
“…In this way, we seek to capture the pedagogic staff’s assessment of the programme, which is highly relevant in process evaluations at this level, as it has a direct influence on the degree of implementation and maintenance [ 34 , 35 , 36 ]. The effect evaluation of potential outcomes at the end-user level has been addressed elsewhere [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Little research has been published on community-wide interventions promoting infants' motor development, compared to children of, for example, kindergarten age and preschoolers [46]. Previous research in infants has primarily focused on those born preterm [47,48].…”
Section: Comparison With the Literaturementioning
confidence: 99%